The reimagined PhD : navigating twenty-first century humanities education - Horinko, Leanne M.; Reed, Jordan M.; Van Wyck, James M. (Rutgers University Press, 2021)
"Long seen as proving grounds for professors, PhD programs have begun to shed this singular sense of mission. Prompted by poor placement numbers and guided by the efforts of academic organizations, administrators and faculty are beginning to feel called to equip students for a range of careers. Yet, graduate students, faculty, and administrators often feel ill-prepared for this pivot. The Reimagined PhD assembles an array of professionals to address this difficult issue. The contributors show that students, faculty, and administrators must collaborate in order to prepare the 21st century PhD for a wide range of careers. The volume also undercuts the insidious notion that career preparation is a zero sum game in which time spent preparing for alternate careers detracts from professorial training. In doing so, The Reimagined PhD normalizes the multiple career paths open to PhD students, while providing practical advice geared to help students, faculty, and administrators incorporate professional skills into graduate training, build career networks, and prepare PhDs for a variety of careers"--